Patients' Financially Driven Delay of GP Visits: Is It Less Likely to Occur in Stronger Primary Care Systems?. (June 2018) - Detollenaere, Jens; Van Pottelberge, Amelie; Hanssens, Lise; Boerma, Wienke; Greß, Stefan; Willems, Sara
Available evidence has suggested that strong primary care (PC) systems are associated with better outcomes. This study aims to investigate whether PC strength is specifically related to the prevalence of patients' financially driven postponement of general practitioner (GP) care. Therefore, data from a cross-sectional multicountry study in 33 countries among GPs and their patients were analyzed using multilevel logistic regression modelling. According to the results, the variation between countries in the levels of patients' postponement of seeking GP care for financial reasons was large. More than one third of these cross-country differences could be explained by characteristics of the health care system and the GP practices. In particular, PC systems with good accessibility and those systems that offer comprehensive care were associated with lower levels of financially driven delay. Consequently, we can conclude that well-organized PC systems can compensate for the negative influence of individual characteristics (socioeconomic position) on the care-seeking behaviors of patients.